STABLE DEVELOPMENT AND ECONOMIC GROWTH IN ANGOR DISTRICT (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
As of April 1, 2025, the Angor district of Surkhandarya region comprises 36 citizens’ assemblies (mahallas), including 26,223 households with 37,515 families. The total population of the district has reached 147.7 thousand people. Under the leadership of Hokim Qosim Mardonov, a wide range of initiatives aimed at ensuring socio-economic stability, improving infrastructure, and promoting entrepreneurship have been successfully implemented in the region.